ANALISIS KESUKARAN SISWA SMP KELAS Vlll DALAM MENGERJAKAN SOAL PADA MATERI STATISTIKA - Selvia Agina; Neng Cucu Nurmaenah; Luvy Sylviana Zanthy (IKIP Siliwangi, 2020)
This study aim to analyse student difficulties in solving problem in statistic lesson. The type of research is qualitive method with descriptive qualitative approach. This study was implemented at SMPN 1 Batujajar with subject 9D with amount 32 student. Data collection technique in this study using documentation method are student test result with main course of statistic, and data analysis conducted, namely assessing student answers based on the tests given, determining the types of errors in answering questions and the number of types of student errors. Based on the research and discussion, Level mathematical ability of student at SMPN 1 Batujajar that is 44,5% which including in medium category. Difficulties experienced by student are found in the indicators of analyzing data from data distribution that is given from percentage diffifulty level student in solving problem in the mount of 80%. It is because student have found difficulties in turning story problem into mathematical models.